2009
DOI: 10.2353/jmoldx.2009.090022
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of KRAS Mutations in Archived Formalin-Fixed Paraffin-Embedded Tissue Using Mutant-Enriched PCR and Reverse-Hybridization

Abstract: Recently, evidence has emerged indicating that assessment of KRAS mutations before anti-epidermal growth factor receptor therapy improves outcome in patients with metastatic colorectal cancer (CRC). We report here a novel reverse-hybridization (RH) assay to screen for KRAS mutations in formalin-fixed paraffin-embedded colorectal tissue samples. We combined mutant-enriched PCR based on peptide nucleic acid clamping and RH of amplification products to nitrocellulose test strips that contained a parallel array of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 22 publications
3
40
0
Order By: Relevance
“…With this technique, mutations were detected in samples containing as little as 1% tumor cells in a wild-type background. These results are in agreement with previous reports using cell lines 11 in which the same sensitivity was found for mutation detection.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…With this technique, mutations were detected in samples containing as little as 1% tumor cells in a wild-type background. These results are in agreement with previous reports using cell lines 11 in which the same sensitivity was found for mutation detection.…”
Section: Discussionsupporting
confidence: 93%
“…The KRAS StripAssay as recently described by Ausch et al 11 was performed according to the manufacturer's instructions (Vienna Labs, Vienna, Austria). Briefly summarized, a PCR enriched for mutant KRAS alleles is performed.…”
Section: Kras Stripassaymentioning
confidence: 99%
See 1 more Smart Citation
“…26,30,32,[34][35][36]50,51 Array/strip assays appear to reach the highest sensitivity, with some assays detecting 0.1% mutant DNA. [45][46][47][48][49] Conversely, HRM, SSCP, and DGGE often show relatively high false-positive rates compared to other techniques and often require additional testing with different methodologies to confirm the mutation detected. 24,26,30,38,[41][42][43][44] These techniques hold value for large-volume screening protocols, such as research applications, but provide little value in most molecular diagnostic laboratory applications.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated high sensitivities and specificities of up to 100%. [45][46][47][48] Interestingly, like sequencing, this technique can detect rare cases where a given sample has more than one type of KRAS mutation, although it only detects those mutations present on the analysis strip. Due to the high sensitivity of the assays, this technique has been successfully applied to KRAS mutation detection in samples that are likely to contain large amounts of nonmutant DNA, including blood and feces.…”
Section: Array or Strip Assay For Kras Mutation Detectionmentioning
confidence: 99%